The role of the principal in implementing the Kurikulum Merdeka at the driving school SDN 004 Sungai Piring, Batang Tuaka district, Indragiri Hilir regency - Indra Gunawan; Sri Kartikowati; Afrianto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The school principal plays a strategic role in determining the direction and success of a school. This study explores the principal's role in implementing the Independent Curriculum (Kurikulum Merdeka) at SDN 004 Sungai Piring, Batang Tuaka District, Indragiri Hilir Regency. A qualitative descriptive research method was used, with data collected through observations, interviews, and documentation. The research subjects included the principal, class teachers, staff, and administrative personnel. Data validity was ensured using the triangulation method, and data analysis was conducted through data reduction, data presentation, and conclusion drawing/verification. The findings indicate that the school principal's leadership is crucial in effectively implementing the Kurikulum Merdeka. The principal is key in facilitating curriculum adoption, guiding teachers, and fostering an environment that supports independent learning. Additionally, strong leadership ensures that teachers and staff understand and apply the curriculum effectively, improving overall school performance. The study concludes that the principal's role extends beyond administrative duties, encompassing mentorship, supervision, and policy enforcement, all of which significantly contribute to the success of the Kurikulum Merdeka.